Ethnomedicinal Plants for Anti-inflammatory and Analgesic in Osing Tribe, East Java, Indonesia: A Review - Firnanda Rayhan Syah Falaini; Arum Suproborini; Yaya Sulthon Aziz; Weka Sidha Bhagawan (LPPM Akafarma Sunan Giri Ponorogo, 2026)
The traditional medicinal knowledge of the Osing people in East Java, Indonesia, particularly concerning plants for inflammation and pain, is not systematically documented, hindering its scientific validation and potential integration into modern healthcare. This review aims to systematically document the ethnomedicinal plants used by the Osing community for anti-inflammatory and analgesic purposes, correlate this knowledge with existing scientific evidence, and perform taxonomic validation. A descriptive method was employed by collecting ethnomedicinal data from the RISTOJA (Riset Tumbuhan Obat dan Jamu) database. This was followed by a comprehensive literature review using scientific databases (PubMed, Google Scholar, ScienceDirect) to gather pharmacological evidence, and taxonomic verification was conducted using the World Flora Online (WFO) database. The study identified 40 plant species from 29 families traditionally used to treat various inflammatory and pain-related conditions, with Curcuma longa L. being the most frequently cited. The scientific validation revealed that 38 of these species (95%) have reported anti-inflammatory or analgesic activities, confirming the empirical knowledge of the Osing people. The findings highlight a strong correlation between traditional use and pharmacological evidence and identify Tectaria subpedata and Ruellia napifera as promising candidates for future research due to a lack of current scientific data. This research validates Osing ethnobotanical knowledge and provides a basis for developing novel phytopharmaceutical products.